Mechanical and thermal characterisation of AlSi10Mg SLM block support structures. (5th December 2019) - Leary, Martin; Maconachie, Tobias; Sarker, Avik; Faruque, Omar; Brandt, Milan
Abstract: Selective Laser Melting (SLM) is an Additive Manufacturing (AM) process based on the local fusion of powdered metal. SLM requires support structures that enable heat transfer and structural support during fabrication while being frangible to enable removal. Despite the criticality of support structures, very little quantitative data exists to characterise their behaviour. AlSi10Mg is an important SLM alloy which is particularly appropriate for laser applications due to its ease of processing. Block support structures are the most versatile of the commercially implemented support structure designs. This research presents an experimental study of the mechanical strength and numerical analysis of the thermal behaviour during SLM fabrication of ALSi10Mg block support structures. It was found that: support structure peel strength is significantly lower than normal strength due to fundamentally different failure mechanisms; support strength is influenced by height; and, reduced support spacing increases heat transfer and load bearing capability. Design equations were generated to enable prediction of the strength of a given support structure. This previously unavailable data allows AM designers to unambiguously specify support structures that are optimal for a specific design scenario. Furthermore, these insights potentially allow the redesign of block support structures such that response is independent of geometry. Graphical abstract: Unlabelled Image Highlights: Analysis of the mechanical strength and thermal properties of AlSi10Mg block support structures fabricated by SLM. The peel strength of a support structure is significantly less than its tensile strength. The strength of a support structure is inversely proportional to its height. Reducing support spacing increases heat transfer capability.